The Evangelical Baptist movement in Belarus in historical research: towards the question of terminological discourse - Lisouskaya, Tatyana V. (Journal of the Belarusian State University. History, 2026)
This article systematises existing approaches to the nomination of the Evangelical Baptist in historical research and substantiates the choice of a term that most appropriately reflects the genesis, evolution, and confessional identity of the movement within the context of the religious history of Belarus. It is revealed that a distinctive feature of the nomination of Protestant movements is the multiplicity of approaches. It is established that in academic and socio-political discourse, the terms «sect», «late Protestantism», «neo-Protestantism», and «new religious movements» are used to describe the Evangelical Baptist. It is concluded that for historical research examining the genesis, evolution, and institutional formation of the Evangelical Baptist in Belarus in the 19th–21st centuries, the most relevant term is «late Protestantism». It captures the place of Evangelical Baptist in the historical development of Protestantism, designates the chronological framework of their emergence (17th–19th centuries), has no evaluative connotations, and allows for a distinction to be made between the Evangelical Baptist, neo-Protestantism, and new religious movements of the late 20th century. This term ensures scientific objectivity and takes into account the dynamics of the institutional development of the Evangelical Baptist from a sectarian form to a denomination.
Keywords: Belarus; late Protestantism; neo-Protestantism; new religious movements; Evangelical Baptists; sect